2022
DOI: 10.1007/s00404-022-06515-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and survival of patients with uterine sarcoma: a German unicenter analysis

Abstract: Purpose Uterine sarcoma (US) as a histologically heterogeneous group of tumors is rare and associated with poor prognosis. Prognostic factors based on systematic data collection need to be identified to optimize patients’ treatment. Methods This unicenter, retrospective cohort study includes 57 patients treated at the University Hospital Freiburg, Germany between 1999 and 2017. Progression-free survival (PFS) and overall survival (OS) were calculated and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Some studies reported that regimens of ifosfamide [11,35,36] or doxorubicin [11,32,36] were effective for uterine sarcoma and decreased the risk of metastasis. Some researchers found that adjuvant chemotherapy was associated with decreased survival [12,37], while others showed better pelvic control and survival rate in adjuvant chemotherapy than those who did not receive either adjuvant chemotherapy or radiotherapy after TH-BSO [11,14,33]. In our study, 76.7% of patients received chemotherapy or chemoradiotherapy after surgery, yet adjuvant therapy didn't affect their survival, which was similar to previous studies [38][39][40].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some studies reported that regimens of ifosfamide [11,35,36] or doxorubicin [11,32,36] were effective for uterine sarcoma and decreased the risk of metastasis. Some researchers found that adjuvant chemotherapy was associated with decreased survival [12,37], while others showed better pelvic control and survival rate in adjuvant chemotherapy than those who did not receive either adjuvant chemotherapy or radiotherapy after TH-BSO [11,14,33]. In our study, 76.7% of patients received chemotherapy or chemoradiotherapy after surgery, yet adjuvant therapy didn't affect their survival, which was similar to previous studies [38][39][40].…”
Section: Discussionsupporting
confidence: 88%
“…Preoperative diagnosis is usually di cult due to the lack of speci c symptoms and diagnostic techniques [1]. So far, most researches on the relationship between risk factors, adjuvant treatment and survival were conducted in western countries [12][13][14][15][16], but much less is known about such association in China [17]. Our retrospective study provided insights into the clinicopathological features and prognosis factors of 75 Chinese uterine sarcoma patients over 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sarcoma prognosis, tumor injury during excision and uncontained morcellation, electric or manual, in both laparotomy and laparoscopy [30][31][32], plays a critical role in upgrading metastasis, resulting in poorer prognosis [33][34][35][36][37]. Hence, several prognostic factors for all histological uterine sarcoma types have been identified, including patient age, tumor stage, mitotic index, vascular invasion, and tumor-free resection margins.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the evidence suggests that PR receptor negativity is a negative prognostic factor in leiomyosarcoma. Patients with PR-negative tumors are more likely to have a shorter survival time than patients with PR-positive tumors (23,24).…”
Section: Prognosis Of Patients With Uterine Leiomyosarcoma (Ulms) Bas...mentioning
confidence: 99%